Prison Education: Beyond Review and Evaluation - Flynn, Nick (The prison journal, 2022)
Much is made of the potential of prison education to impart knowledge and skills and transform life chances. Prison education is tasked with delivering qualifications and effecting recidivism. In assessing current arrangements for the delivery of prison education and reviews and evaluations of its impact on recidivism in England and Wales, this article argues that prison education should be an inclusive activity. Specifically, prison education should focus less on individual development and more on whole class ‘domains,’ in particular, knowledge of (re)integration. Research, policy, and practice on civic/citizenship education provide models in this regard.